Leprosy: International public health policies and public health eras - Niyi Awofeso (Administrative Sciences, 2011)
Public health policies continue to play important roles in national and international health reforms. However, the influence and legacies of the public health eras during which such policies are formulated remain largely underappreciated. The limited appreciation of this relationship may hinder consistent adoption of public health policies by nation-states, and encumber disinvestment from ineffective or anachronistic policies. This article reviews seven public health eras and highlights how each era has influenced international policy formulation for leprosy control-"the fertile soil for policy learning". The author reiterates the role of health leadership and health activism in facilitating consistency in international health policy formulation and implementation for leprosy control.
Keywords: 350; public health eras; international public health policies; leprosy